2008
DOI: 10.1063/1.2832991
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Highly Nonlinear Signals in a Two Dimensional Network of Granular Chains

Abstract: Abstract.We report the first experimental observation of highly nonlinear signals propagating in a two dimensional system composed of granular chains. In this system one of the chains contacts two others to allow splitting and redirecting the solitary-like signal formed in the first chain. The system consists of a double Y-shaped guide in which high-and low-modulus chains of spheres are arranged in various geometries. We observed fast splitting of the initial pulse, rapid chaotization of the signal and sharp b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In particular, previous studies have suggested that nonlinear granular crystals can act as effective media for shock/impact mitigation, owing to their ability to trap [7,15], localize [16,17], redirect [18,19], and redistribute energy [20]. These capabilities are based on the complex dynamic behavior of granular chains composed of particles of different materials and geometry.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, previous studies have suggested that nonlinear granular crystals can act as effective media for shock/impact mitigation, owing to their ability to trap [7,15], localize [16,17], redirect [18,19], and redistribute energy [20]. These capabilities are based on the complex dynamic behavior of granular chains composed of particles of different materials and geometry.…”
Section: Introductionmentioning
confidence: 98%
“…Solitary waves were demonstrated capable of following a bent trajectory, and could split after crossing the bifurcated interface. Arrangements of particles composed of heterogeneous materials were also shown capable of trapping and delaying pulses [ 18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Such systems have been proposed for a variety of engineering applications, including energy trapping and impulse disintegration [8,9,13,17]. Two-dimensional systems composed 361 of spherical particles arranged in a Y-shaped configuration were also investigated [ 18,19]. In these systems, a symmetric Yshaped guide was used to analyze the propagating of single and multiple highly nonlinear solitary waves, in both uniform and heterogeneous arrangements of particles.…”
Section: Introductionmentioning
confidence: 99%
“…Granular crystals also have been proposed for a variety of engineering applications, including energy trapping and impulse disintegration [8,10,15,16,20], nondestructive evaluation [6,21], and sound focusing devices [22]. Few attempts have been made to study the propagation of highly solitary waves in two-dimensional (2D) systems [23][24][25][26][27]. In particular, systems composed of spherical particles arranged in a symmetric Y-shaped configuration at fixed branch angles also have been studied [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Few attempts have been made to study the propagation of highly solitary waves in two-dimensional (2D) systems [23][24][25][26][27]. In particular, systems composed of spherical particles arranged in a symmetric Y-shaped configuration at fixed branch angles also have been studied [24][25][26]. The study of the dynamics of branched systems showed that highly nonlinear solitary waves can follow a bent trajectory, and they can split when crossing a Y junction.…”
Section: Introductionmentioning
confidence: 99%